Deep financial integration and volatility - Sebnem Kalemli-Özcan; Bent E. Sørensen; Vadym Volosovych (TÜSİAD-Koç University Economic Research Forum, 2010)
We investigate the relationship between financial integration and output volatility at micro and macro levels. Using a very large firm-level dataset (AMADEUS) from 16 European countries, we construct a measure of deep financial integration at the regional level based on observations of foreign ownership at the firm-level. We find a significant positive effect of foreign ownership on the volatility of firms' outcomes in static as well as dynamic empirical frameworks. This effect survives aggregation and carries over to regional output, leading to a positive association between deep financial integration and aggregate fluctuations. To identify the causal effect of financial integration on volatility we exploit variation in the transposition dates of the European Union-wide legislative acts from the Financial Services Action Plan (FSAP). We find that high trust regions located in countries who harmonized their capital markets sooner have increased levels of financial integration and volatility.
Keywords: E32; F15; F36; O16; 330; firm volatility; foreign ownership; regional integration; social capital; macro volatility; Finanzmarkt; Wirtschaftsintegration; Unternehmensentwicklung; Industrielle Produktion; Volatilität; EU-Staaten